1996
DOI: 10.1080/00103629609369713
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the time‐domain reflectometer and determination of the volumetric water content of the soil profile in an ultisol of Costa Rica

Abstract: An experiment was conducted to determine if time-domain reflectometry (TDR) could be used to measure the water content at different depths in the O-to-75 cm soil layer. Probes of three wires (1/8 inch diameter and 30 cm exposed length) were installed in field plots differing in current crop-fertilization history. Measurements of volumetric water content using bulk density and gravimetric water content were made to calibrate the TDR method. Comparison of water contents determined by TDR with those from gravimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Indeed, on applying two-way ANOVA, a significant difference between both data sets was found (degrees of freedom = 1; 201; P = 8.2´10 -6 ; table III); TDR afforded slightly underestimated values of q as compared to NP (0.218 versus 0.222 cm 3 cm -3 ). Salas et al [25] also found that TDR underestimated q.…”
Section: Comparison Between Soil-profile Moistures Obtained With Bothmentioning
confidence: 87%
See 3 more Smart Citations
“…Indeed, on applying two-way ANOVA, a significant difference between both data sets was found (degrees of freedom = 1; 201; P = 8.2´10 -6 ; table III); TDR afforded slightly underestimated values of q as compared to NP (0.218 versus 0.222 cm 3 cm -3 ). Salas et al [25] also found that TDR underestimated q.…”
Section: Comparison Between Soil-profile Moistures Obtained With Bothmentioning
confidence: 87%
“…Also, the increase in soil bulk-density with depth, which leads to greater soil homogeneity [11,15], could contribute to the improvement of the results with depth. Salas et al [25] also observed greater differences between the gravimetric and TDR techniques for the first 30 cm of soil depth (greater heterogeneity).…”
Section: Comparison By Depthsmentioning
confidence: 90%
See 2 more Smart Citations